2016
DOI: 10.1007/s00221-016-4724-3
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory perceptual learning is dependent upon task difficulty

Abstract: There has been a growing interest in developing behavioral tasks to enhance temporal acuity as recent findings have demonstrated changes in temporal processing in a number of clinical conditions. Prior research has demonstrated that perceptual training can enhance temporal acuity both within and across different sensory modalities. Although certain forms of unisensory perceptual learning have been shown to be dependent upon task difficulty, this relationship has not been explored for multisensory learning. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
(70 reference statements)
3
19
0
Order By: Relevance
“…Overall, the daily exposure to the training stimuli pairings (e.g., TOJ task: ±200 ms SOA; SJ task: 0 and 200 ms SOA) may have resulted in the rats re-learning the association between the stimuli pairings within their new perceptual state (i.e., impaired hearing sensitivity from hearing loss), which ultimately led to a perceptual recalibration of audiovisual perception. Support for this suggestion comes from previous studies on normal-hearing participants which found that engagement in perceptual training paradigms that included trial-by-trial feedback (like in the present study) led to an improved ability to detect asynchronous audiovisual stimuli, thus resulting in a narrower temporal window of integration (Powers et al, 2009 ; De Niear et al, 2016 , 2018 ). Future studies are needed to determine whether exposure to training stimuli is necessary for the preservation of audiovisual perception.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Overall, the daily exposure to the training stimuli pairings (e.g., TOJ task: ±200 ms SOA; SJ task: 0 and 200 ms SOA) may have resulted in the rats re-learning the association between the stimuli pairings within their new perceptual state (i.e., impaired hearing sensitivity from hearing loss), which ultimately led to a perceptual recalibration of audiovisual perception. Support for this suggestion comes from previous studies on normal-hearing participants which found that engagement in perceptual training paradigms that included trial-by-trial feedback (like in the present study) led to an improved ability to detect asynchronous audiovisual stimuli, thus resulting in a narrower temporal window of integration (Powers et al, 2009 ; De Niear et al, 2016 , 2018 ). Future studies are needed to determine whether exposure to training stimuli is necessary for the preservation of audiovisual perception.…”
Section: Discussionsupporting
confidence: 77%
“…It would be reasonable to predict that moderate hearing loss—which reduces one’s sensitivity to environmental sounds—could distort audiovisual temporal acuity due to the fact that varying the intensity (effectiveness) of auditory and/or visual stimuli is known to alter perceptual judgments in normal-hearing participants (Smith, 1933 ; Neumann et al, 1992 ; Neumann and Niepel, 2004 ; Boenke et al, 2009 ; Krueger Fister et al, 2016 ). That said, it is well-established that the perceptual binding of audiovisual stimuli is highly-adaptive to experience, as evidenced from research on participants who were passively exposed to asynchronous audiovisual stimuli (Fujisaki et al, 2004 ; Navarra et al, 2005 ; Vatakis et al, 2007 , 2008b ), as well as those actively engaged in perceptual training (Powers et al, 2009 ; De Niear et al, 2016 , 2018 ). Thus, an alternative prediction could be that individuals who experience adult-onset hearing loss may show limited changes to their audiovisual temporal acuity, owed to a recalibration of their perceptual ability as they adapt to their permanent hearing impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Surig et al (2018) varied the task difference of a two-alternative forced-choice SJT (either at each participant’s individual threshold or randomly chosen) and discovered faster improvements in the ‘adaptive’ condition regarding the processing speed of auditory inputs as well as the size of the ventriloquist effect. De Niear et al (2016) altered the task difficulty of a SJT and observed that enhancements in temporal acuity could be optimized by employing audio-visual stimuli for which it is difficult to judge temporal synchrony. In another study, De Niear et al (2018) showed that perceptual training was capable of enhancing temporal acuity for simple stimuli (‘flashes’ and ‘beeps’) as well as for more complex speech stimuli (the phoneme ‘ba’).…”
Section: Introductionmentioning
confidence: 99%
“…A number of future investigations could evaluate these relationships. Studies have shown that multisensory training paradigms with feedback can result in the narrowing of the TBW and increased functional connectivity between the STS and regions of the auditory and visual cortices in typically developed individuals [De Niear, Gupta, Baum, & Wallace, 2018; De Niear, Koo, & Wallace, 2016; Powers 3rd et al, 2012; Powers, Hillock, & Wallace, 2009]. Work has just begun to investigate if these same paradigms result in improved neural and behavioral multisensory function in individuals with ASD [Feldman et al, 2020], and plan to assess if these effects result in lasting changes to other domains such as social communication.…”
Section: Translational Approaches For Asd: Relationships Between Multmentioning
confidence: 99%
“…parvalbumin‐positive interneurons) are reversibly silenced through optogenetic techniques [Olcese et al, 2013], does this result in impaired social function or the presence of repetitive/restricted behavior? The development of multisensory operant tasks in mice [Meijer et al, 2018; Siemann et al, 2015] also raises the opportunity to evaluate whether training in animal models can improve multisensory function, which may parallel approaches being developed in humans that seek to capitalize on multisensory training [De Niear et al, 2016; De Niear et al, 2018; Powers 3rd et al, 2012; Powers et al, 2009].…”
Section: Translational Approaches For Asd: Relationships Between Multmentioning
confidence: 99%